2014
DOI: 10.1186/1475-9276-13-39
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic differences in self-rated health among women: a comparison of St. Petersburg to Estonia and Finland

Abstract: IntroductionSocial determinants of health have not been intensively studied in Russia, even though the health divide has been clearly demonstrated by an increased mortality rate among those with low education. A comparative analysis of social health determinants in countries with different historical and economic backgrounds may provide useful evidence for addressing health inequalities. We aimed to assess socioeconomic determinants of self-rated health in St. Petersburg as compared to Estonia and Finland.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…According to the literature, the proportion of poor SRH is the result of the processes that involve several factors. Education level is an important modulator of this phenomenon (3,29). In bivariate analysis, the results of the present study demonstrated that the individuals with low levels of education had worse health status, which is in 2…”
Section: Discussionmentioning
confidence: 55%
“…According to the literature, the proportion of poor SRH is the result of the processes that involve several factors. Education level is an important modulator of this phenomenon (3,29). In bivariate analysis, the results of the present study demonstrated that the individuals with low levels of education had worse health status, which is in 2…”
Section: Discussionmentioning
confidence: 55%
“…Self-rated health (SRH) is not only usually used to measure the health status of the population and health inequalities within that populations [13], but it is also used as a predictor of morbidity, mortality and health services utilization [46]. Literature from Western countries reports a socio-economic gradient in SRH with improvements in health status correlated with an increase in socio-economic status [79].…”
Section: Introductionmentioning
confidence: 99%
“…In the study, I used a socio-economic status (SES) because many previous studies have been reporting that the relationship between health and socioeconomic factors explain a lot of the differences in SRH (Mackenbach, 2008;Dubikaytis et al, 2014;Richter, Moor,& van Lenthe, 2010;Tsimbos, 2010;Dinesen et al, 2011;Alvarez-Galvez et al, 2013). Principal Component Analysis was used as an algebraic operation for reducing dimensionality and computing one variable, combining three main parameters of SES: the highest level of education (which is expressed in terms of the International Standard Classification of Education (ISCED)), occupation (using the International Standard Classification of Occupations (ISCO88)), and subjective income (using the questions about how respondents felt about household income).…”
Section: Discussionmentioning
confidence: 99%